High Concentration and Frequent Application of Disinfection Increase the Detection of Methicillin-Resistant Staphylococcus aureus Infections in Psychiatric Hospitals During the COVID-19 Pandemic - Yang, Mi; Feng, Yu; Yuan, Lu; Zhao, Huachang; Gao, Shan; Li, Zezhi (Frontiers in Medicine, 2021)
While the requirements of environmental disinfection have been raised in the high-risk areas of medical institutions during the COVID-19 pandemic, the tolerance of certain multi-drug resistant bacteria to disinfectants may be promoted. The current research addressed the mechanisms underlying a sharp increase in the detection of methicillin-resistant Staphylococcus aureus (MRSA) observed in a closed-management unit of elderly patients with mental disorders in 2020 as compared to the previous four years. We first conducted microbial detection in staff-hand and environment and a molecular epidemiology analysis, rejecting the hypothesis that the MRSA increase was due to an outbreak. Then, we turned to disinfectant concentration and frequency of use and analyzed the varied MRSA detection rates with different concentrations and frequencies of disinfection in 2020 and the previous four years. The MRSA detection rate increased with elevated concentration and frequency of disinfection (1000 mg/L or 500 mg/L twice per day since January in 2020 vs. 500 mg/L 2-3 times per week in 2016-2019). When the disinfectant concentration was reduced from 1000mg/L to 500mg/L, the MRSA detection decreased, indicating a modulatory role of disinfectant concentration. With sustained frequency of disinfection in 2020, the MRSA detection rate was still higher, even after May, than that in the previous years, suggesting that frequency of disinfection also contributed to the MRSA increase. Overall, the MRSA detection was augmented with the increase in disinfection concentration and frequency during the COVID19 epidemic, suggesting that highly-concentrated and highly-frequent preventive long-term disinfection is not recommended without risk assessments in psychiatric hospitals.